Methanogenesis in an impacted and two dystrophic coastal lagoons (Macaé, Brazil) - Furtado,André Luiz dos Santos (2002)
This study investigated the methanogenic activity in sediment of the Imboacica (human impacted), Cabiúnas and Comprida coastal lagoons in Rio de Janeiro State (Brazil). Methane was not detected in water and sediment samples from the three lagoons. The measured nutrient concentrations in the pore-water indicated that methanogens activity was not limited by nutrients. Methanogenic activity was not detected under in vitro conditions, indicating that terminal organic carbon mineralisation via methanogenesis was negligible for the top 6 cm of sediment at the sampling time.